2022
DOI: 10.1038/s41392-021-00859-y
|View full text |Cite
|
Sign up to set email alerts
|

Ionizable liposomal siRNA therapeutics enables potent and persistent treatment of Hepatitis B

Abstract: Small interfering RNA (siRNA) constitutes a promising therapeutic modality supporting the potential functional cure of hepatitis B. A novel ionizable lipidoid nanoparticle (RBP131) and a state-of-the-art lyophilization technology were developed in this study, enabling to deliver siRNA targeting apolipoprotein B (APOB) into the hepatocytes with an ED50 of 0.05 mg/kg after intravenous injection. In addition, according to the requirements of Investigational New Drug (IND) application, a potent siRNA targeting hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…Rapid and efficient endosomal escape plays an essential role in siRNA delivery. [ 13 , 25 ] It was reported that ROS generated upon irradiation could interact with the lysosome/endosome membrane and facilitate siRNA escaping into the cytoplasm. It was assumed that ROS photogeneration in this study would disrupt both NEO and lysosome/endosome membrane, leading to effective siRNA escape and cytosolic release.…”
Section: Resultsmentioning
confidence: 99%
“…Rapid and efficient endosomal escape plays an essential role in siRNA delivery. [ 13 , 25 ] It was reported that ROS generated upon irradiation could interact with the lysosome/endosome membrane and facilitate siRNA escaping into the cytoplasm. It was assumed that ROS photogeneration in this study would disrupt both NEO and lysosome/endosome membrane, leading to effective siRNA escape and cytosolic release.…”
Section: Resultsmentioning
confidence: 99%
“…A prototypical application area is the LNP (lipid‐based nanoparticle) field, which has gained substantial momentum after the successful development and global application of LNP formulated mRNA vaccines for Covid19 (Baden et al., 2020 ). RNA encapsulation efficiencies by empty LNPs are typically determined indirectly such as by non‐membrane permeable RNA intercalating dyes (Huang et al., 2022 ; Michel et al., 2017 ; Wu et al., 2008 ), or fractions of RNA co‐isolating with liposomes, quantified by RT‐qPCR (Saha et al., 2018 ; Tsuji et al., 2016 ). We reasoned that quantitative single particle imaging enabled by EVAnalyzer might provide a straightforward and direct method to characterise RNA encapsulation at the single particle level.…”
Section: Resultsmentioning
confidence: 99%
“…During lyophilization, the removal of water takes place via sublimation at low temperature under vacuum. Generally, lyophilization is comparatively a mild drying method and believed to enhance the stability issues mostly related to colloidal nanoparticles (NPs) and/or macro-biomolecules [145,146].…”
Section: Storage Issue Related To Mrna Vaccinesmentioning
confidence: 99%